Comparative effectiveness of pemafibrate versus bezafibrate on hepatic and vascular endothelial function in patients with coronary artery disease and metabolic dysfunction-associated steatotic liver disease - Nakamura, Akihiro; Kagaya, Yuta; Saito, Hiroki; Kanazawa, Masanori; Miura, Masanobu; Kondo, Masateru; Endo, Hideaki (Frontiers in Endocrinology, 2026)
BackgroundPeroxisome proliferator-activated receptor (PPAR) agonists are promising therapeutic agents for metabolic dysfunction-associated steatotic liver disease (MASLD), which increases cardiovascular risk.MethodsWe compared the efficacy of pemafibrate, a highly selective PPAR-α agonist, and bezafibrate, a non-selective PPAR-α agonist, in patients with coronary artery disease (CAD) and MASLD. This was a post-hoc analysis of a randomized, crossover study that treated hypertriglyceridemia with pemafibrate or bezafibrate for 24 weeks, followed by a crossover for another 24 weeks. Of the 60 enrolled patients, 21 were identified as having MASLD (fatty liver index [FLI] ≥ 60 and hepatic steatosis index [HSI] ≥ 36 as indicators). The primary outcomes were changes in serum alanine aminotransferase (ALT) levels and flow-mediated dilation (FMD). Secondary outcomes were changes in the FLI and HSI. Homeostasis model assessment of insulin resistance (HOMA-IR) was assessed as an exploratory outcome.ResultsThe percentage reduction in ALT levels was significantly greater with pemafibrate treatment than with bezafibrate treatment (−23.1% vs. −9.2%, P = 0.035). FMD significantly increased in both groups, with no difference in the magnitude of the percentage change (P = 0.267). FLI significantly decreased in both groups with no difference in the magnitude of change (P = 0.983), while HSI was not significantly different before and after treatment in either group. Both treatments significantly lowered HOMA-IR; however, the decrease was similar between the groups (P = 0.724).ConclusionsPemafibrate is more effective than bezafibrate at reducing ALT levels while offering similar beneficial effects on insulin resistance and endothelial function in CAD patients with MASLD.